2009
DOI: 10.1186/1471-2164-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and functional analysis of altered molecular pathways in human atherosclerotic arteries

Abstract: BackgroundAtherosclerosis affects aorta, coronary, carotid, and iliac arteries most frequently than any other body vessel. There may be common molecular pathways sustaining this process. Plaque presence and diffusion is revealed by circulating factors that can mediate systemic reaction leading to plaque rupture and thrombosis.ResultsWe used DNA microarrays and meta-analysis to study how the presence of calcified plaque modifies human coronary and carotid gene expression. We identified a series of potential hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 58 publications
5
73
0
Order By: Relevance
“…Interestingly, analysis of expression profile studies using human genomic microarrays shows significant up-regulation of TRPC3 mRNA levels in plaques derived from patients with atherosclerotic lesions in the left anterior descendent coronary artery (31). In circulating monocytes from three out of four patients homozygous for familial hypercholesterolemia, the TRPC3 mRNA was notoriously up-regulated compared with heterozygous or control patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, analysis of expression profile studies using human genomic microarrays shows significant up-regulation of TRPC3 mRNA levels in plaques derived from patients with atherosclerotic lesions in the left anterior descendent coronary artery (31). In circulating monocytes from three out of four patients homozygous for familial hypercholesterolemia, the TRPC3 mRNA was notoriously up-regulated compared with heterozygous or control patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…A number of chemoattractant cytokines, such as macrophage inflammatory protein (MIP)-1β, MIP-1α, monocyte chemotactic proteins and regulated upon activation, normal T cell expressed and secreted (RANTES) [3], may participate in signaling the entry of adherent monocytes into the artery wall, where they accumulate lipid and transform into macrophage foam cells. In one study, high levels of MIP-1β were found in plasma of atherosclerotic patients [4]. MIP-1β gene expression has been found to be elevated in Kawasaki disease [5] and heart failure [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the genes reported mainly focus on aspects of regulation of cell apoptosis (8)(9)(10), growth (11), mobility (12), inflammation (13), and signal transduction (14,15), while the mechanisms of lipid droplet (LD) formation were largely ignored or underestimated in these studies. Disorders of lipid homeostasis have been seen as the major factors influencing atherosclerotic traits (16), including cholesterol clearance from foam cells, removal of fatty acids and lipoproteins, and lipid transportation in cell organelles. The most recent studies have proven that LD-associated proteins contribute to the regulation of cellular lipid stores, nascent LD biogenesis and lipid metabolism and transport (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%